Diabetes and Pregnancy: Epidemiological surveillance - Pacora, Percy (2015)
The prevalence of gestational diabetes mellitus (GDM) reaches 2% by screening a Peruvian pregnant population. Performing standard Oral glucose tolerance test (OGTT) on 17540 Peruvian pregnant women with risk factors for diabetes at San Bartolome’s Hospital in Lima, the prevalence of GDM was 3,8%, it represented 1% of all pregnancies with antenatal care and 0,5% of all the deliveries attended over that period 95% of GDM were gestational diabetes (DG) and 5% pregestational diabetes (DPG). Fasting blood sugar over 79 mg1dL (4,5 mM/L) could have diagnosed GDM at the first visit with 93% sensitivity and 80% of specificity and is more sensitive to identify pregnancies at increased risk than OGTT using National Diabetes Data Group’s Criteria. We advocate to perform OGTT in pregnancies without diabetes risk factor at 20-26 weeks of gestation using 1 glucose/kg weight, considering as normal: fasting blood sugar 85 mg/dL, 1 hour 140 mg/dL and 2 hours 120 mg/dL. One abnormal value is diagnostic and these patients should recieve prompt treatment. We recommend pregestational education, birth control before conception in order to achieve euglycemia, early diagnosis of pregnancy, tight-metabolic control, and team-management including the family during pregnancy.